Peran Mediasi Hedonic Value Dalam Hubungan Antara Flash Sale, Fear of Missing Out (FOMO), Terhadap Perilaku Impulsive Buying Konsumen Aerostreet - Muhammad Hasbi Arrofiq; Kisti Nur Aliyah (Universitas Muhammadiyah Pontianak, 2026)
This study aims to analyze the effect of flash sales and fear of missing out (FOMO) on impulsive buying behavior with hedonic value as a mediating variable among Aerostreet consumers. The study uses a quantitative approach with data obtained from 160 respondents through an online survey and analyzed using PLS-SEM. The results show that flash sales and FOMO have a positive and significant effect on impulsive buying, both directly and indirectly through hedonic value. These findings confirm that emotional factors and shopping experiences play an important role in driving impulsive buying.